Blockchain Applications and Institutional Trust - Smits, Martin; Hulstijn, Joris (Frontiers in Blockchain, 2020)
In the current discussions around Blockchain and distributed ledger technologies, we find a lack of theory to conceptualize and understand application scenarios. In this paper we propose to conceptualize distributed ledger technologies as trust mechanisms. Whereas previously one had to rely on a trusted third party (e.g. notary), now one must trust a complex software system – the Blockchain and distributed ledger application– as well as the parties that host the software system and ensure its effectiveness. Based on theories of e-commerce, business networks, and trust, we explore relations between trust and Blockchain design. We analyze three case studies of Blockchain applications in the diamond industry. In each case we study two complementary research questions: (1) how does the blockchain application influence trust, and (2) how do trust based requirements affect the design of a blockchain application? We formulate two propositions and find dynamic interactions between trust requirements, blockchain application design, and transaction trust.